2011
DOI: 10.1039/c1em10364d
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations in particle size fractions from street dust of Murcia (Spain) as the basis for risk assessment

Abstract: Street dust has been sampled from six different types of land use of the city of Murcia (Spain). The samples were fractionated into eleven particle size fractions (<2, 2-10, 10-20, 20-50, 50-75, 75-106, 106-150, 150-180, 180-425, 425-850 μm and 850-2000 μm) and analyzed for Pb, Cu, Zn and Cd. The concentrations of these four potentially toxic metals were assessed, as well as the effect of particle size on their distribution. A severe enrichment of all metals was observed for all land-uses (industrial, suburban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(36 citation statements)
references
References 43 publications
9
26
0
1
Order By: Relevance
“…The physicochemical properties analyzed (Tables 1, 2), in general, fall into the range of values comparable to what has been found in other cities of the world where pH, C оrg content and EC varied between 7-9, 1-17%, and 100-2800 μS/cm, respectively (Wang and Qin 2007;Al-Khashman 2007;Ladonin and Plyaskina 2009;Acosta et al 2011;Yisa et al 2011;Hu et al 2011;Sutherland et al 2012).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The physicochemical properties analyzed (Tables 1, 2), in general, fall into the range of values comparable to what has been found in other cities of the world where pH, C оrg content and EC varied between 7-9, 1-17%, and 100-2800 μS/cm, respectively (Wang and Qin 2007;Al-Khashman 2007;Ladonin and Plyaskina 2009;Acosta et al 2011;Yisa et al 2011;Hu et al 2011;Sutherland et al 2012).…”
Section: Resultssupporting
confidence: 78%
“…Extensive literature is devoted to elemental composition of road dust; however, the physicochemical properties inherited from its different components have been studied to a much lesser extent, although they are the ones that determine the potential of the dust to fix pollutants. Usually, such parameters as pH, organic carbon content (C оrg ), electrical conductivity (EC), and particle size distribution are evaluated (Wang and Q in , 2007;Al-Khashman 2007;Hu et al 2011;Acosta et al 2011). The studies of atmospheric dust focus on particles with an aerodynamic diameter of 10 μm or smaller (PM 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the findings of Herath et al (2013) who also reported high organic matter content in Colombo metropolitan region due waste disposal, leakage of lubricants and vehicle oil. Further, the present study is also in agreement with the work of Karmacharya and Shakya (2012) and Acosta et al (2011) who reported similar results in properties of street dust.…”
Section: Dust Propertiessupporting
confidence: 93%
“…The observed levels of difference in the present study were most likely due to variation in the sources of metals. The present results are comparable with the work of Acosta et al (2011) who reported higher concentration of Zn (205 mg/kg) in dust of industrial area and Pb (85 mg/kg) in highways. Besides, the results are supported by Ambade (2012) as well found higher concentration of Zn in dust of industrial environment of Bhilai city, India.…”
Section: Heavy Metal Concentrations In Street Dustsupporting
confidence: 90%
“…Imperato et al, 2003;Acosta et al, 2011;Sun et al, 2010). To our knowledge, few studies have focused on the fractionation and mobility of heavy metals in contaminated urban soils (Burt et al, 2014;Acosta et al, 2015;Gu et al, 2016), and even less their availability in soil and transfer to earthworms (Pizl and Josens, 1995;Kennette et al, 2002;Nannoni et al, 2011).…”
Section: Introductionmentioning
confidence: 98%